2015
DOI: 10.1175/jcli-d-14-00615.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of ENSO on Northern Midlatitude Ozone during the Winter to Spring Transition

Abstract: The influence of El Niño-Southern Oscillation (ENSO) on northern midlatitude ozone during the period January-March (JFM) is investigated using various observations and a chemistry-climate model. The analysis reveals that, during El Niño events, there are noticeable anomalously high total ozone column (TOC) values over the North Pacific, the southern United States, northeastern Africa, and East Asia but anomalously low values in central Europe and over the North Atlantic. La Niña events have almost the opposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
1
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 86 publications
6
40
1
7
Order By: Relevance
“…Therefore, it is necessary to examine the trend of the geopotential height and the large-scale dynamical processes responsible for such a trend. Figure 4a shows the differences of geopotential height and horizontal winds Zhang et al 2015). It should be pointed out that the above mentioned large-scale dynamical processes affecting TCO are also presented in the LOTM.…”
Section: Zonally Asymmetric Ozone Trend and Its Influencing Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, it is necessary to examine the trend of the geopotential height and the large-scale dynamical processes responsible for such a trend. Figure 4a shows the differences of geopotential height and horizontal winds Zhang et al 2015). It should be pointed out that the above mentioned large-scale dynamical processes affecting TCO are also presented in the LOTM.…”
Section: Zonally Asymmetric Ozone Trend and Its Influencing Factorsmentioning
confidence: 98%
“…Indeed, many previous studies have demonstrated the important role of planetary waves in modulating ZAO variations (e.g. Peters and Entzian 1999;Peters et al 2008;Efstathiou et al 2003;Hio and Yoden 2004;Grytsai et al 2005;Gabriel et al 2011;Ialongo et al 2012;Zhang et al 2015) and have proposed that the planetary waves of tropospheric origin could affect TCO through tropopause height modulations and stratosphere-troposphere exchange processes. Nevertheless, whether and to what extent planetary wave changes exert an influence on the zonally asymmetric TCO trend in the past 30 years remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not known whether the impact of ASO extends to the tropics, for example, to influence the El Niño-Southern Oscillation (ENSO), a major climatic mode of tropical variability (e.g., Jin 1996, Timmermann et al 1999, Ashok and Yamagata 2009, Latif and Keenlyside 2009, Yeh et al 2009) that has great global climatic and societal impacts (e.g., Orlove et al 2000, McPhaden et al 2006, Deser et al 2010. It is well known that ENSO can influence tropical ozone through anomalous convection (Camp et al 2003, Xie et al 2014 and the high-latitude stratospheric ozone (Bȑonnimann et al 2004, Eyring et al 2006, Zhang et al 2015 through anomalous propagation and dissipation of ultra-long Rossby waves at mid-latitudes (Gettelman et al 2001, Calvo et al 2004, Manzini et al 2006, Garfinkel and Hartmann 2008, Randel et al 2009, Hurwitz et al 2011, Xie et al 2012. Figure 1 shows the lead-lag correlation coefficients at three-monthly intervals between the ENSO index and zonally averaged ozone, for ENSO variations leading ozone by 3 months to lagging ozone by 24 months.…”
Section: Introductionmentioning
confidence: 99%
“…The leading global mode of interannual variability in the transport is the El Niño-Southern Oscillation (ENSO) pattern (Zhang et al, 1997). The impact of ENSO on tropical and extratropical tropospheric ozone has been detected from satellite observations (Ziemke et al, 2010(Ziemke et al, , 2015 and is captured by global models (Oman et al, 2011;Zhang et al, 2015), but has not been observed at the surface. However, the ability of models of atmospheric composition to correctly respond to this large-scale forcing may be a critical test of their performance.…”
Section: Climate-chemistry Modes Of Variabilitymentioning
confidence: 99%